Evaluation of adenoviral vector Ad19a encoding RSV-F as novel vaccine against respiratory syncytial virus - Fuchs, Jana; Hübner, Julian; Schmidt, Anna; Irrgang, Pascal; Maier, Clara; Vieira Antao, Ana Isabel; Oltmanns, Friederike; Thirion, Christian; Lapuente, Dennis; Tenbusch, Matthias (npj Vaccines, 2024)
Respiratory syncytial virus (RSV) is the leading cause of severe lower respiratory tract infections in infants and toddlers. Since natural infections do not induce persistent immunity, there is the need of vaccines providing long-term protection. Here, we evaluated a new adenoviral vector (rAd) vaccine based on the rare serotype rAd19a and compared the immunogenicity and efficacy to the highly immunogenic rAd5. Given as an intranasal boost in DNA primed mice, both vectors encoding the F protein provided efficient protection against a subsequent RSV infection. However, intramuscular immunization with rAd19a vectors provoked vaccine-enhanced disease after RSV infection compared to non-vaccinated animals. While mucosal IgA antibodies and tissue-resident memory T-cells in intranasally vaccinated mice rapidly control RSV replication, a strong anamnestic systemic T-cell response in absence of local immunity might be the reason for immune-mediated enhanced disease. Our study highlighted the potential benefits of developing effective mucosal against respiratory pathogens.
CRIS-Team Scopus Importer:2024-11-15

Filling two needs with one deed: a combinatory mucosal vaccine against influenza A virus and respiratory syncytial virus - Vieira Antao, Ana Isabel; Oltmanns, Friederike; Schmidt, Anna; Viherlehto, Vera; Irrgang, Pascal; Rameix-Welti, Marie-Anne; Bayer, Wibke; Lapuente, Dennis; Tenbusch, Matthias (Frontiers in Immunology, 2024)
Influenza A Virus (IAV) and Respiratory Syncytial Virus (RSV) are both responsible for millions of severe respiratory tract infections every year worldwide. Effective vaccines able to prevent transmission and severe disease, are important measures to reduce the burden for the global health system. Despite the strong systemic immune responses induced upon current parental immunizations, this vaccination strategy fails to promote a robust mucosal immune response. Here, we investigated the immunogenicity and efficacy of a mucosal adenoviral vector vaccine to tackle both pathogens simultaneously at their entry site. For this purpose, BALB/c mice were immunized intranasally with adenoviral vectors (Ad) encoding the influenza-derived proteins, hemagglutinin (HA) and nucleoprotein (NP), in combination with an Ad encoding for the RSV fusion (F) protein. The mucosal combinatory vaccine induced neutralizing antibodies as well as local IgA responses against both viruses. Moreover, the vaccine elicited pulmonary CD8+ and CD4+ tissue resident memory T cells (TRM) against the immunodominant epitopes of RSV-F and IAV-NP. Furthermore, the addition of Ad-TGFβ or Ad-CCL17 as mucosal adjuvant enhanced the formation of functional CD8+ TRM responses against the conserved IAV-NP. Consequently, the combinatory vaccine not only provided protection against subsequent infections with RSV, but also against heterosubtypic challenges with pH1N1 or H3N2 strains. In conclusion, we present here a potent combinatory vaccine for mucosal applications, which provides protection against two of the most relevant respiratory viruses.
CRIS-Team Scopus Importer:2024-07-12
Keywords: adjuvant; combinatory vaccine; influenza A virus (IAV); mucosal immunity; respiratory syncytial virus (RSV); respiratory viruses

Influence of AAV vector tropism on long-term expression and Fc-γ receptor binding of an antibody targeting SARS-CoV-2 - Wagner, Jannik; Müller-Schmucker, Sandra; Wang, Wenjun; Arnold, Philipp; Uhlig, Nadja; Issmail, Leila; Eberlein, Valentina; Damm, Dominik; Roshanbinfar, Kaveh; Enßer, Armin; Oltmanns, Friederike; Peter, Antonia Sophia; et al. (Communications Biology, 2024)
Long-acting passive immunization strategies are needed to protect immunosuppressed vulnerable groups from infectious diseases. To further explore this concept for COVID-19, we constructed Adeno-associated viral (AAV) vectors encoding the human variable regions of the SARS-CoV-2 neutralizing antibody, TRES6, fused to murine constant regions. An optimized vector construct was packaged in hepatotropic (AAV8) or myotropic (AAVMYO) AAV capsids and injected intravenously into syngeneic TRIANNI-mice. The highest TRES6 serum concentrations (511 µg/ml) were detected 24 weeks after injection of the myotropic vector particles and mean TRES6 serum concentrations remained above 100 µg/ml for at least one year. Anti-drug antibodies or TRES6-specific T cells were not detectable. After injection of the AAV8 particles, vector mRNA was detected in the liver, while the AAVMYO particles led to high vector mRNA levels in the heart and skeletal muscle. The analysis of the Fc-glycosylation pattern of the TRES6 serum antibodies revealed critical differences between the capsids that coincided with different binding activities to murine Fc-γ-receptors. Concomitantly, the vector-based immune prophylaxis led to protection against SARS-CoV-2 infection in K18-hACE2 mice. High and long-lasting expression levels, absence of anti-drug antibodies and favourable Fc-γ-receptor binding activities warrant further exploration of myotropic AAV vector-based delivery of antibodies and other biologicals.
CRIS-Team Scopus Importer:2024-07-26

Mucosal tumor vaccination delivering endogenous tumor antigens protects against pulmonary breast cancer metastases - Oltmanns, Friederike; Vieira Antao, Ana Isabel; Irrgang, Pascal; Viherlehto, Vera; Jörg, Leticia; Schmidt, Anna; Wagner, Jannik; Rückert, Michael; Flohr, Ann-Sophie; Geppert, Carol-Immanuel; Frey, Benjamin; Bayer, Wibke; et al. (Journal for ImmunoTherapy of Cancer, 2024)
Background Generally, early-stage breast cancer has a good prognosis. However, if it spreads systemically, especially with pulmonary involvement, prospects worsen dramatically. Importantly, tumor-infiltrating T cells contribute to tumor control, particularly intratumoral T cells with a tissue-resident memory phenotype are associated with an improved clinical outcome. Methods Here, we use an adenoviral vector vaccine encoding endogenous tumor-associated antigens adjuvanted with interleukin-1β to induce tumor-specific tissue-resident memory T cells (TRM) in the lung for the prevention and treatment of pulmonary metastases in the murine 4T1 breast cancer model. Results The mucosal delivery of the vaccine was highly efficient in establishing tumor-specific TRM in the lung. Concomitantly, a single mucosal vaccination reduced the growth of pulmonary metastases and improved the survival in a prophylactic treatment. Vaccine-induced TRM contributed to these protective effects. In a therapeutic setting, the vaccination induced a pronounced T cell infiltration into metastases but resulted in only a minor restriction of the disease progression. However, in combination with stereotactic radiotherapy, the vaccine increased the survival time and rate of tumor-bearing mice. Conclusion In summary, our study demonstrates that mucosal vaccination is a promising strategy to harness the power of antitumor TRM and its potential combination with state-of-the-art treatments.
CRIS-Team Scopus Importer:2024-03-22

Mucosal vaccination with a viral vector vaccine induces robust lung-resident T cell responses and protects against 4T1 metastasis - Oltmanns, Friederike; Vieira Antao, Ana Isabel; Irrgang, P.; Meyn, V.; Jörg, Leticia; Tenbusch, Matthias; Lapuente, Dennis (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Protective mucosal immunity against SARS-CoV-2 after heterologous systemic prime-mucosal boost immunization - Lapuente, Dennis; Fuchs, Jana; Willar, Jonas; Vieira Antao, Ana Isabel; Eberlein, Valentina; Uhlig, Nadja; Issmail, Leila; Schmidt, Anna; Oltmanns, Friederike; Peter, Antonia Sophia; Müller-Schmucker, Sandra; Irrgang, Pascal; et al. (Nature Communications, 2021)
Several effective SARS-CoV-2 vaccines are currently in use, but effective boosters are needed to maintain or increase immunity due to waning responses and the emergence of novel variants. Here we report that intranasal vaccinations with adenovirus 5 and 19a vectored vaccines following a systemic plasmid DNA or mRNA priming result in systemic and mucosal immunity in mice. In contrast to two intramuscular applications of an mRNA vaccine, intranasal boosts with adenoviral vectors induce high levels of mucosal IgA and lung-resident memory T cells (TRM); mucosal neutralization of virus variants of concern is also enhanced. The mRNA prime provokes a comprehensive T cell response consisting of circulating and lung TRM after the boost, while the plasmid DNA prime induces mostly mucosal T cells. Concomitantly, the intranasal boost strategies lead to complete protection against a SARS-CoV-2 infection in mice. Our data thus suggest that mucosal booster immunizations after mRNA priming is a promising approach to establish mucosal immunity in addition to systemic responses.
CRIS-Team Scopus Importer:2021-12-10

Protective mucosal immunity against SARS-CoV-2 after heterologous systemic RNA-mucosal adenoviral vector immunization - Lapuente, Dennis; Fuchs, Julian; Willar, J.; Antao, A.; Eberlein, V.; Uhlig, N.; Issmail, L.; Schmidt, Anna; Oltmanns, Friederike; Peter, Anne; Müller-Schmucker, Sandra; Irrgang, P.; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27